The Concept of Human Actions in Muhammad Asad's Interpretation: A Study of 'The Message of the Qur'an (Study of the Book of Tafsir for Thinking People) - Muhammad Reza Hardiansyah; Kharis Nugroho; Andri Nirwana, A.N. (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to find out Muhammad Asad's interpretation in The Message of the Qur'an, to verses related to human deeds. Muhammad Asad in his commentary, prioritizes the understanding that human beings are given the freedom to choose their actions (free will), but he is still responsible for these choices before Allah. Asad emphasized that the Qur'an not only provides moral and ethical guidance, but also provides space for man to develop in his awareness of his duty in the world and the world. In general, Asad focuses on the following understanding: Asad interprets verses that mention man's freedom to choose his actions as a gift from God, where man is given the freedom to choose his way of life. In this case, man is fully responsible for the actions he chooses. Second, in his interpretation, Asad refers to the concept of man as the caliph (representative) of Allah on earth. Therefore, humans must shoulder moral and social responsibilities in living life in the world. Third, Asad highlighted that every deed done by man will be rewarded according to his intentions and deeds. Good or bad deeds always have great spiritual consequences. Fourth, Asad also emphasized that in understanding human actions, every human action that has an impact on society must also be carried out with awareness of the values of goodness and justice outlined in the Qur'an.